An Update on Mesenchymal Stem Cell-Centered Therapies in Temporomandibular Joint Osteoarthritis - Yifan Zhao; Liang Xie (Stem Cells International)
Temporomandibular joint osteoarthritis (TMJOA) is a degenerative disease characterized by cartilage degeneration, disrupted subchondral bone remodeling, and synovitis, seriously affecting the quality of life of patients with chronic pain and functional disabilities. Current treatments for TMJOA are mainly symptomatic therapies without reliable long-term efficacy, due to the limited self-renewal capability of the condyle and the poorly elucidated pathogenesis of TMJOA. Recently, there has been increased interest in cellular therapies for osteoarthritis and TMJ regeneration. Mesenchymal stem cells (MSCs), self-renewing and multipotent progenitor cells, play a promising role in TMJOA treatment. Derived from a variety of tissues, MSCs exert therapeutic effects through diverse mechanisms, including chondrogenic differentiation; fibrocartilage regeneration; and trophic, immunomodulatory, and anti-inflammatory effects. Here, we provide an overview of the therapeutic roles of various tissue-specific MSCs in osteoarthritic TMJ or TMJ regenerative tissue engineering, with an additional focus on joint-resident stem cells and other cellular therapies, such as exosomes and adipose-derived stromal vascular fraction (SVF). Additionally, we summarized the updated pathogenesis of TMJOA to provide a better understanding of the pathological mechanisms of cellular therapies. Although limitations exist, MSC-centered therapies still provide novel, innovative approaches for TMJOA treatment.